Solitons of Some Nonlinear Sigma-Like Models - Vekslerchik, V.E. (Symmetry, Integrability and Geometry: Methods and Applications, 2020)
We present a set of differential identities for some class of matrices. These identities are used to derive the 𝑁-soliton solutions for the Pohlmeyer nonlinear sigma-model, two-dimensional self-dual Yang-Mills equations and some modification of the vector Calapso equation.